The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2478/s11686-013-0105-2
|View full text |Cite
|
Sign up to set email alerts
|

Falcaustra sanjuanensis sp. nov. (Nematoda: Kathlaniidae) from Odontophrynus cf. barrioi (Anura: Cycloramphidae) from Argentina

Abstract: Here, we describe a new kathlaniid nematode, Falcaustra sanjuanensis sp. nov., from the large intestine of Odontophrynus cf. barrioi (Anura: Cycloramphidae), from San Juan Province, Argentina. The new species belongs to the Falcaustra group that possesses a pseudosucker. It resembles F. andrias in the distribution pattern of caudal papillae (six precloacal, four adcloacal, 12 postcloacal, one unpaired median anterior to the cloaca) but differs from F. andrias in the following characters: the longer size of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In tadpoles of Allophryne ruthveni , the m. levator mandibulae externus is present in two slips, with the superficialis inserting in the adrostral tissue mass, and the profundus inserting on the suprarostral ala. Given the presence of these two slips in leptodactylids (e.g., Haas 2003 ; Vera Candioti 2007 ; Vera Candioti et al 2007 ), odontophrynids (e.g., Haas 2003 ; Gonzalez et al 2014 ; Dias et al 2019 ; Dias 2020 ), and bufonids (e.g., Haas 2003 ; Vera Candioti 2007 ; Aguayo et al 2009 ; Haad et al 2014 ), the loss of the secondary slip of the m. levator mandibulae externus is a putative synapomorphy of Centrolenidae.…”
Section: Tadpole Morphologymentioning
confidence: 99%
“…In tadpoles of Allophryne ruthveni , the m. levator mandibulae externus is present in two slips, with the superficialis inserting in the adrostral tissue mass, and the profundus inserting on the suprarostral ala. Given the presence of these two slips in leptodactylids (e.g., Haas 2003 ; Vera Candioti 2007 ; Vera Candioti et al 2007 ), odontophrynids (e.g., Haas 2003 ; Gonzalez et al 2014 ; Dias et al 2019 ; Dias 2020 ), and bufonids (e.g., Haas 2003 ; Vera Candioti 2007 ; Aguayo et al 2009 ; Haad et al 2014 ), the loss of the secondary slip of the m. levator mandibulae externus is a putative synapomorphy of Centrolenidae.…”
Section: Tadpole Morphologymentioning
confidence: 99%
“…The information available on metazoan parasites of the herpetofauna from the Monte desert in Argentina mostly refers to helminth species found in reptiles (Ramallo and Díaz, 1998;Ramallo et al, 2002a;2002b;2016a;2017;Goldberg et al, 2004). Regarding helminths found in amphibians, González et al (2013a) described the nematode Falcaustra sanjuanensis González, Sanabria and Quiroga, 2013 from the large intestine of Odontophrynus cf. barrioi and González et al (2013b) reported the nematode Aplectana hylambatis (Baylis, 1927) Travassos, 1931 from the large intestine of Rhinella arenarum Hensel, 1867.…”
Section: Introductionmentioning
confidence: 99%